Association between Ambient Air Pollution by Particulate Matter (PM2.5) and Vehicular Traffic in Downtown Port City of Tampico, Mexico - Mariela Estefania Nava-Velez; Bárbara A. Macías-Hernández; Edgar Tello-Leal; René Ventura-Houle (Environmental Sciences Proceedings, 2023)
The objective of this study was to statistically analyze the concentration of pollution in the air by PM2.5 particulate matter and vehicular traffic using a methodology based on quadrants, considering the periods of “working” and “holiday” activities in the downtown area from the port city of Tampico, Mexico. The vehicular traffic count was carried out in three hourly ranges per day for a week in each period. Moreover, an analysis of the correlation coefficient based on the Spearman method was carried out, both in the working and vacation periods, between the variables of PM2.5 concentration and total vehicular traffic by the hourly range and by day in each quadrant. A strong to very strong correlation (0.828 ≥ r ≤ 0.960) was identified between pollutant concentration and vehicular traffic on several days and quadrants in the work period. On the other hand, in the holiday period, a weak to moderate correlation was observed on most of the days considered in this study.